Free Vibration Analysis of Thick Rectangular and Elliptical Plates with Concentric Cut-Out. (16th October 2021) - Merneedi, Anjibabu; Mohan Rao, Nalluri; Natrayan, L.; Yuvaraj, L.; Paramasivam, Prabhu
Abstract : This research paper deals with a numerical method which is modified and applied, by the authors to derive an eigenvalue of a thick plate having cut-out in which geometries of plate and cut-outs are different, through a deflection matching condition by including shear deformation and rotary inertia effects, with less computational efforts and high accuracy. The modified Independent Coordinate Coupling Method (ICCM) is validated with FEM package (ANSYS) and applied to know the change in eigenvalues for a plate with cut-out by varying various parameters like aspect ratios, cut-out size, and thickness ratios. Trigonometric functions considered at the boundary level conditions of a simply supported plate should be satisfied. Free vibrational exploration on a thick isotropic plate with various aspect ratios and an elliptical plate with various sizes is carried out through the modified ICCM. Independent coordinates are applied for a plate domain and for a hole domain individually followed by equating the deflection condition of hole and plate, a reduced mass to express with cut-out from which eigenvalues can be obtained. The deflection matching condition facilitates the analysis even though the geometries of plate and cut-outs are different.